Examining the Covid-19 Coping Strategies Employed by Residents in Selected South Africa’s Rural Areas - Okem, Andrew Emmanuel; MUBANGIZI, BETTY CLAIRE; Adekanla, N; John, SF; Ibrahima, B (SPCRD Global Publisihing, 2023)
Rural communities are vulnerable to shocks associated with the COVID-19 pandemic. The resilience of these communities depends on their ability to cope with the impacts of such shocks. This study examines the COVID-19 coping strategies of residents of Matatiele and Winnie Madikizela Mandela local municipalities in South Africa. We collected primary data through 11 FGDs and 13 individual interviews. Of the six coping strategies identified, the most cited was resorting to alternative food sources to address food insecurity. Other coping strategies include alternative sources of income; reducing remittance and expenditure; shifting to new activities; and introducing emotional support. The findings reveal that coping strategies entail changes around basic needs such as food and income. To protect these communities against future shocks, strong local institutions working in collaboration will be invaluable in empowering communities to identify and implement alternative livelihoods while building supportive infrastructure.
N/A
N/A